Pyrolysis and mass spectrometry studies of meteoritic organic matter. - Sephton,MA (Mass Spectrom Rev, 2012)
Meteorites are fragments of extraterrestrial materials that fall to the Earth's surface. The carbon-rich meteorites are derived from ancient asteroids that have remained relatively unprocessed since the formation of the Solar System 4.56 billion years ago. They contain a variety of extraterrestrial organic molecules that are a record of chemical evolution in the early Solar System and subsequent aqueous and thermal processes on their parent bodies. The major organic component (>70%) is a macromolecular material that resists straightforward solvent extraction. In response to its intractable nature, the most common means of investigating this exotic material involves a combination of thermal decomposition (pyrolysis) and mass spectrometry. Recently the approach has also been used to explore controversial claims of organic matter in meteorites from Mars. This review summarizes the pyrolysis data obtained from meteorites and outlines key interpretations. © 2012 Wiley Periodicals, Inc. Mass Spec Rev 31:560-569, 2012.